Screening of diabetic respiratory symptomatics for pulmonary TB: a key to tackle another hurdle in patient care and TB control? - Jalamkar, Omprakash D.; Salve, Vijay Tukaram (International Journal Of Community Medicine And Public Health, 2017)
Background: Association of diabetes and TB have been described in literature since ancient times. With the effective AIDS control programme, HIV related TB morbidity and mortality has decreased drastically, globally as well as in India. However with current life style, diabetes is increasing. And diabetes related TB, is one of the major hurdle in control of TB at both patient care to public health level. Bidirectional screening has been advocated by WHO and IUATLD. The purpose of this study is to revisit the problem of ‘TB and DM duo’. Methods: Hundred consecutive diabetic respiratory symptomatics, attending medical and chest outpatient department and referrals at ESI-post-graduate institute at a tertiary hospital, Mumbai, were enrolled as per inclusion and exclusion criteria and data was collected and analyzed. Data was compared with the similar studies in literature and final conclusion was drawn. Results: From our experience, 15% diabetics having respiratory symptoms were diagnosed as PTB. Majority of patients had ‘typical radiological findings ‘(i.e. upper zone predilection) and 50% of the diagnosed TB patients had +1 smear. Poor glycemic control was found to be associated with PTB (mean HbA1c -9.5%, S.D -1.866). Conclusions: Diabetes possess a significant burden on pulmonary TB and a serious consideration and due priority should be given to screen diabetic respiratory symptomatics as part of collaborative diabetes TB management.